Isolation and identification of lactobacillus from selected Malaysians fermented foods / Mohd Nur Saiful Abdul Samad - Abdul Samad, Mohd Nur Saiful (Faculty of Applied Sciences, 2014)
Lactic acid bacteria are the types of bacteria that produce lactic acid. The classification of lactic acid bacteria into two major groups is based on the end-product that is resulted from the fermentation process. Tempoyak, cencalok, budu and rebung are among the few traditional foods in Malaysia that is very popular for the local people. The aim of this study was to isolate and identify the Lactobacillus from these four types of fermented foods. The result of this study showed that all these fermented foods consist of Lactobacillus and among these four different types of food, tempoyak were producing the most potential Lactobacillus. The existence of bacteria in the Malaysian fermented foods was detected by using several biochemical tests. To check for which fermented foods that were producing the most potential Lactobacillus, the viable plate count method has been used in this study.